TRABALHO DE CAMPO NO VALE DO JEQUITINHONHA: UMA POSSIBILIDADE DE APROXIMAÇÃO DA REALIDADE DO CAMPO - Martins, Maria de Fátima Almeida; Coelho, Ana Maria Simões (Geografares, 2010)
DOI: 10.7147/GEO8.1296